STUDENTS PERSPECTIVES ON STUDYING AT UNIVERSITY: A QUALITATIVE STUDY USING SELF-DETERMINATION AND PLANNED BEHAVIOR THEORIES - Ahmad Azmi Abdel Hamid Esmaeil; Ismail Maakip; Peter Voo; Abu Huraerah (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2024)
Abstract. This research attempts to explore students' perceptions about continuing their studies at university. As well as understanding why they continue their studies and why they choose a particular study program. This study has used a qualitative method for the purpose of deepening the perceptions conveyed by the respondents of this study. This study has interviewed a total of 15 students from one of the IPTA in Malaysia, thematic analysis has been used in the data analysis. The results of the study found that many students consider studying at university as a place to develop their minds and personalities. In addition, the findings of the study also found that students gain specialized knowledge especially in the field or program they choose. Universities must also provide a conducive environment and ensure development especially for academic staff to facilitate student learning. The findings of the study also found that students enter university for various reasons, such as pursuing interests or worrying about their future jobs. While other respondents stated that they entered the university to meet the demands of their families or to follow their friends. Finally, respondents chose a university based on a particular program because they found it easy or because it was the only option available to them. Although most of the respondents are more focused on self-improvement, most of those who come to university are based on their own future and limited options.Keywords: Self determination, Planned behavior, Qualitative Method, University Student, Higher Education in Malaysia. Abstrak. Penelitian ini coba untuk mengeksplorasi persepsi mahasiswa tentang melanjutkan studi di universitas. Serta memahami alasan mereka melanjutkan studi dan alasan memilih program studi tertentu. Penelitian ini menggunakan metode kualitatif dengan tujuan untuk memperdalam persepsi yang disampaikan oleh responden penelitian ini. Penelitian ini telah mewawancarai total 15 mahasiswa salah satu IPTA di Malaysia, analisis tematik digunakan dalam analisis data. Hasil penelitian menemukan bahwa banyak mahasiswa yang menganggap kuliah di universitas sebagai tempat untuk mengembangkan pikiran dan kepribadiannya. Selain itu, temuan penelitian juga menemukan bahwa mahasiswa memperoleh pengetahuan khusus terutama pada bidang atau program yang mereka pilih. Perguruan tinggi juga harus menyediakan lingkungan yang kondusif dan menjamin pengembangan khususnya bagi tenaga akademik untuk memfasilitasi pembelajaran mahasiswa. Temuan penelitian ini juga menemukan bahwa mahasiswa masuk universitas karena berbagai alasan, seperti mengejar minat atau khawatir akan pekerjaan masa depan mereka. Sedangkan responden lainnya menyatakan masuk perguruan tinggi karena memenuhi tuntutan keluarga atau mengikuti teman-temannya. Terakhir, responden memilih universitas berdasarkan program tertentu karena mereka merasa mudah atau karena itu adalah satu-satunya pilihan yang tersedia bagi mereka. Meskipun sebagian besar responden lebih fokus pada pengembangan diri, sebagian besar dari mereka yang masuk universitas didasarkan pada masa depan mereka sendiri dan pilihan yang terbatas.Kata Kunci: Determinasi diri, perilaku terencana, studi kualitatif, mahasiswa, perguruan tinggi Malaysia.